PENGARUH METODE LOCI TERHADAP KEMAMPUAN MENGINGAT PELAJARAN IPA PADA SISWA KELAS V SD - Syanthi Syanthi; Christina Hiunata; Sherly Sherly; Jennifer Claudia (Universitas Bunda Mulia, 2016)
Memorizing has become part of students’ study activities in learning. As the learning program is getting harder for primary students, they have got difficulties for maintaining what they see and hear for long time. Method of loci is known as one of mnemonic method that helps student to memorize. Method of loci is a memorizing technique which we can associate the words with familiar places. The method in this research is experimental research with between subject designs. The sample of this research is two groups of fifth grade students. Experimental group was taught by method of loci and control group was taught by reading to memorize the science learning subject. The ability to memorize was measured by giving the achievement test to students. Data was analyzed by Mann- whitney, the results revealed p = 0,0337 (p < 0,05), the experiment group memorize better than the control group. This meant teaching science with method of loci can help students to memorize the learning content better than reading. Keywords: Method of Loci, Memorizing Ability, Learning, Fifth Grade Students